Analysis of Participatory Development in Implementing Decentralized Waste Management - Halimah, Laili Rahma; Machdum, Sari Viciawati (LP2M INSURI Ponorogo, 2023)
The Bandung City Government encourages participation through the decentralization of waste management. Unfortunately, the TPS 3R Maleer as one of the pilot waste management sites in Bandung City could not promote equal participation in the implementation of decentralized waste management. This study aims to analyse the application of participatory development in the implementation of decentralization waste management in Maleer Village. Based on qualitative approach and a descriptive type, this study explain the stages, mechanisms, and benefits of participatory development. The results showed that the participatory development in decentralized waste management in Maleer Village lack of the community's participation. The participatory development stage from decision-making, implementation, and utilization has been carried done, however we did not see the community involvement in the evaluation stage. Moreover, the participatory development mechanisms have also been carried out through socialization and education, consultation, collaboration, and empowerment of waste management. Unfortunately, this mechanism has not realized sustainable activities due to the low commitment of the community. We found that the lack of community participation in decentralized waste management in Maleer Village is caused by some reasons. Non-formal evaluation did not run regularly and lack coordination in formal evaluation. Then, the low commitment of the community is caused by the lack of public awareness, limited time, limited capacity, and low community intention in sorting waste.